Web-Based Recruitment System Design with K-NN Algorithm at PT Gunung Himun Peratama - Ardiansyah, Alfian; Purnama, Giri (Ali Institute of Research and Publication, 2025)
With the increasing need for workers, the recruitment process has become a crucial aspect in supporting the operations of PT Gunung Himun Peratama. Currently, the selection process is still carried out manually, resulting in delays, inefficiencies, and the potential for human error. This study aims to develop a web-based decision support system by integrating the K-Nearest Neighbor (K-NN) algorithm to improve efficiency and accuracy in the employee selection process. The system development was carried out using the waterfall method, with PHP technology, the CodeIgniter framework, and the MySQL database. The K-NN algorithm is used to calculate the proximity between new applicant data and historical data based on a number of predetermined criteria. System evaluation was carried out through black-box testing and classification accuracy analysis. The results of the study showed that the system was able to classify applicants accurately and reduce the selection time from an average of three days to one day. In addition, the system provides objective acceptance recommendations based on processed historical data, thereby increasing efficiency, transparency, and accountability in the recruitment process. This system makes a real contribution to the development of decision support information systems in the field of human resources